2014
DOI: 10.1007/s10620-014-3113-7
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease Increases Risk for Gastroesophageal Reflux Symptoms

Abstract: Our data show that the prevalence of GERD typical symptoms is higher in patients with NAFLD. GERD was associated with higher BMI and MetS, but not with age and diabetes type 2. NAFLD remained strongly associated with GERD, independently of a coexisting MetS status. Consistent with these findings, MetS can be considered a shared background, but cannot completely explain this correlation. We suggest NAFLD as an independent risk factor for GERD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 58 publications
1
21
0
1
Order By: Relevance
“…Recent studies have suggested that GERD could also be a risk factor for NAFLD although the results were inconsistent. [ 12 13 14 15 16 17 18 19 20 ] To summarize all available data, we conducted this systematic review and meta-analysis of observational studies, which compared the risk of NAFLD among patients with GERD versus those without GERD.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that GERD could also be a risk factor for NAFLD although the results were inconsistent. [ 12 13 14 15 16 17 18 19 20 ] To summarize all available data, we conducted this systematic review and meta-analysis of observational studies, which compared the risk of NAFLD among patients with GERD versus those without GERD.…”
Section: Introductionmentioning
confidence: 99%
“…Several observational studies have yielded controversial findings. 10 Conversely, a cohort study which included 34 063 subjects in South Korea and adjusted for BMI and other metabolic factors found that NAFLD was not independently associated with the risk of reflux oesophagitis (HR 1.01, 95% CI: 0.94-1.09; P = .79), but instead reflux oesophagitis is mainly the consequence of increased BMI commonly associated with NAFLD. 7 Again, a cross-sectional study in Taiwan involving a total of 12 090 individuals and adjusting for multiple risk factors revealed a 1.23-fold increased risk of erosive oesophagitis in patients with NAFLD compared with subjects without NAFLD.…”
Section: Discussionmentioning
confidence: 96%
“…11 Similarly, Catanzaro et al found that NAFLD was linked to an increased prevalence of GERD symptoms in a cross-sectional study totalling 206 subjects and adjusting for multiple potential confounding factors (adjusted OR = 3.49, 95% CI: 2.24-5.44). 10 Conversely, a cohort study which included 34 063 subjects in South Korea and adjusted for BMI and other metabolic factors found that NAFLD was not independently associated with the risk of reflux oesophagitis (HR 1.01, 95% CI: 0.94-1.09; P = .79), but instead reflux oesophagitis is mainly the consequence of increased BMI commonly associated with NAFLD. 14 However, Min et al found a positive association between NAFLD and reflux oesophagitis in a cohort study involving a total of 117 377 Korean adults.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations